Teleworking Technology Adoption in Organizations: Explaining the Role of Social Influence, Motivation and Facilitating Conditions - Alirezaei Alirezaei; Jabarzadeh Jabarzadeh; erfan Haji Akhoondi; hossein RahmanyYoushanlouei (Journal of Information Technology Management)
The aim of this article is to investigate the structural relationship between social influence, motivation and facilitating conditions with the use behaviour of teleworking technology, considering the moderating effect of behavioural intention to utilize teleworking. The research is done according to descriptive method with correlational type. Statistical population is public organizations and the sample was selected using simple random sampling. Data collection tool was questionnaire and experts judged its validity. The reliability of the tool was evaluated using a pre-test of 30 people. The data gathered from a sample of 365 people used to test the hypothesis and conceptual model of the research. By exploratory factor analysis and structural equation model path analysis was done. The results show that social influence, motivation and facilitating conditions have a positive impact on behavioural intention to use teleworking systems and this behavioural intention cause an increase in using behaviour among employees.